138k views
5 votes
If f(x) = 12x+2, then f^-1(x) =??​

2 Answers

3 votes

Answer:


f^(-1)(x) =
(x-2)/(12)

Explanation:

let y = f(x) and rearrange making x the subject, that is

y = 12x + 2 ( subtract 2 from both sides )

y - 2 = 12x ( divide both sides by 12 )


(y-2)/(12) = x

Change y back into terms of x


f^(-1) (x) =
(x-2)/(12)

User Userx
by
5.4k points
2 votes

Explanation:

Given

f(x) = 12x + 2

f^-1(x) = ?

Now

Let y = f(x)

or y = 12x + 2

Interchanging the role of x and y

x = 12y + 2

x - 2 = 12y

y = x - 2

12

Therefore f^-1(x) = x - 2

12

Hope it will help you.

User Darren Stone
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.